Writers, readers, and erasers of N6-Methyladenosine (m6A) methylomes in oilseed rape: identification, molecular evolution, and expression profiling - Chaofan Shan; Kui Dong; Dongyu Wen; Ziyi Ye; Fei Hu; Meryem Zekraoui; Jun Cao (BMC Plant Biology)
Abstract Background m6A RNA modifications are the most prevalent internal modifications in eukaryotic mRNAs and are crucial for plant growth and development, as well as for responses to biotic or abiotic stresses. The modification is catalyzed by writers, removed by erasers, and decoded by various m6A-binding proteins, which are readers. Brassica napus is a major oilseed crop. The dynamic regulation of m6A modifications by writers, erasers, and readers offers potential targets for improving the quality of this crop. Results In this study, we identified 92 m6A-regulatory genes in B. napus, including 13 writers, 29 erasers, and 50 readers. A phylogenetic analysis revealed that they could be further divided into four, three, and two clades, respectively. The distribution of protein motifs and gene structures among members of the same clade exhibited notable similarity. During the course of evolution, whole genome duplication (WGD) and segmental duplication were the primary drivers of the expansion of m6A-related gene families. The genes were subjected to rigorous purification selection. Additionally, several sites under positive selection were identified in the proteins. RNA-seq and quantitative real-time PCR (qRT-PCR) expression analyses revealed that the identified Bnam6As exhibit tissue-specific expression patterns, as well as their expression patterns in response to various abiotic and biotic stresses. The 2000 bp sequence upstream of Bnam6As contained a number of cis-acting elements that regulate plant growth and environmental response. Furthermore, the protein interaction network revealed their interactions with a number of proteins of significant functional importance. Conclusion The identification of m6A modifiers in oilseed rape and their molecular evolution and expression profiling have revealed potential functions and molecular mechanisms of m6A, thus establishing a foundation for further functional validation and molecular breeding.